Antimicrobial resistance pattern of Escherichia coli isolated from imported frozen shrimp in Saudi Arabia - Alhabib, Ibrahim; Elhadi, Nasreldin (PeerJ, 2024)
Contamination of seafood products with multi-drug-resistant (MDR) bacteria is considered to be a potential source for the spread of MDR bacteria in communities. However, little is known about the extent of the contamination of seafood, in particular shrimp, with MDR bacteria in Saudi Arabia. In this study, imported frozen shrimp in retail markets were examined for the antimicrobial susceptibility patterns of Escherichia coli. Escherichia coli was isolated from 40 frozen shrimp samples; a total of 25 and 15 shrimp samples were imported from China and Vietnam, respectively. Of the 40 examined frozen shrimp samples, 30 tested positive for E. coli, resulting in an overall isolation rate of 75%, with a total of 180 isolates being identified. The largest number of positive samples for E. coli isolates (n = 140) were found in 22 out of 25 samples from frozen shrimp imported from China. Additionally, eight out of 15 samples from frozen shrimp imported from Vietnam were positive for E. coli, leading to the recovery of 40 isolates. Overall, the susceptibilities among E. coli isolates were observed against 99.4% for amikacin, augmentin and kanamycin, 95% for cefoxitin and 92.7% for ceftazidime and nitrofurantoin. High percentage of the isolates exhibited resistance to cephalothin (174/180, 96.6%), ampicillin (167/180, 92.7%), Cephalexin (163/180. 90.5%), piperacillin (156/180, 86.6%), ceftriaxone (123/180, 68.3%), nalidixic acid (95/180, 52.7%), trimethoprim sulphamethoxazole (90/180, 50%), and tetracycline (88/180, 48.8%). Additionally, the MDR (resistant to ≥3 different class of antimicrobials) rate among E. coli isolates was 94.4% (170/180). A relatively high intermediate resistance of 60% (108/180) was exhibited for aztreonam. Notably, E. coli showed 71 different antibiotic resistance patterns with the multiple antibiotic resistant (MAR) index ranging from 0.04 to 0.66 and 89.4% of E. coli isolates recorded very significant MAR indexes above the range of 0.2. In this study, we recorded highest antimicrobial co-resistance patterns of 162 (90%) isolates between cephalothin and ampicillin, followed by 158 (87.7%) isolates between cephalothin and cephalexin. Furthermore, and interestingly, the segregation of antimicrobial resistance patterns based on the source of country origin of frozen shrimp revealed few inter-country resistant patterns found interconnecting and this influenced 44 (24.4%) isolates overlapping between isolates origin from frozen shrimp imported from China and Vietnam. This study documents the antimicrobial resistance in E. coli isolated from imported frozen shrimp and the presence of MDR E. coli in shrimp consuming communities, which may pose a risk to public health and the transfer of resistant bacteria to the food chain and environment.
Keywords: E. coli; Imported shrimp; Antimicrobial resistance; Multiple antibiotic resistant index; One-health